2017
DOI: 10.4172/2167-0420.1000365
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Verbal Behavior Style in Interviews in Family Medicine: Mars and Venus, or North Dakota and South Dakota?

Abstract: Objective: To describe and compare the doctor-patient communication referred to the verbal behavior of the female patients vs. males in the family medicine consultation. Participants and Methods:Secondary analysis of existing dataset coded to explore patient-clinician verbal communication during ambulatory visits in a family medicine office in a health Centre in Toledo (Spain) was carried out. The audio recording of the consultations and verbal content analysis of the interviews, based on the identification of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…On the other hand, the verbal behaviours of the women seem to be more useful to obtain better results in the consultation. Women's conversations focus more frequently on feelings, relationships, and personal problems [31] and present more verbal behaviours of "Supporting," and less "Disagreement [7]. We found that the female patients with a companion show 2/3 more verbal behaviours than when the female patients go unaccompanied (165 vs.…”
Section: Verbal Behaviour Of Female Patientsmentioning
confidence: 84%
See 2 more Smart Citations
“…On the other hand, the verbal behaviours of the women seem to be more useful to obtain better results in the consultation. Women's conversations focus more frequently on feelings, relationships, and personal problems [31] and present more verbal behaviours of "Supporting," and less "Disagreement [7]. We found that the female patients with a companion show 2/3 more verbal behaviours than when the female patients go unaccompanied (165 vs.…”
Section: Verbal Behaviour Of Female Patientsmentioning
confidence: 84%
“…The methodology of the study was qualitative, observational, and narrative and has already been described previously [6,7]. Through the audio recording of the consultation, the verbal content of the interviews was analysed, based on the identification of 6 categories of classification of the behaviours in meetings that describe the class or behavioural style of the interaction process, not its content [8]:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, on average, female physicians spend more time with patients than male physicians, some male physicians spend more time with their female patients than female physicians (Roter et al, 1999) and others highlight that female physicians spending more time with patients than male physicians results in the unintended effect of limiting the number of clients that female physicians are able to provide care for (Jefferson et al, 2013). In some contexts, gender does not result in differences in the verbal behavior of female and male physicians (Turabian et al, 2017) and there are many factors, such as the duration of symptoms and the intervention a client receives, that are not impacted by a clinician's gender (Jackson et al, 2003). While gender concordance contributes to improved patient perception of quality of care, some studies suggest it does not impact adherence to provider recommendations (Zhao et al, 2019).…”
Section: Health Studies On Gender Concordancementioning
confidence: 99%